Association between Emission Parameters and Material-phase Concentrations of Phthalate Plasticizers and their Alternatives - Chenyang Bi; Clara M. A. Eichler; Chunyi Wang; John C. Little (Aerosol and Air Quality Research)
Abstract Plasticizers are frequently used in building materials and consumer products and many are semi-volatile organic compounds (SVOCs). Understanding the emission rate of plasticizers in indoor environments is critical for subsequent exposure and health risk assessments. While concerns have been increasing regarding the use of phthalate plasticizers in products and the emission of phthalates has been characterized in previous studies, the emission characteristics of compounds that are now being used as alternatives for phthalates remain poorly understood. In this work, we measured key parameters governing the emission of several phthalates and also their most recent emerging alternatives. Measurements include the gas-phase concentration in equilibrium with the material, y0, and the vapor pressure, p*, using polyvinyl chloride (PVC) sheets with relatively high, but accurately known levels of the material-phase concentration, C0, of the target plasticizers. We found that the PVC sheets containing different plasticizers show varying levels of y0 (0.05–184 µg m−3) despite having the same material-phase concentrations (C0 = 32.9% w/w). We further examined the influence of high material-phase concentrations on y0 and found that the measured concentrations of y0 of diisononyl phthalate (DINP) (i.e., 0.12, 0.13, and 0.13 µg m−3) for three PVC sheets were almost the same despite having different material-phase levels (i.e., 39%, 33%, and 26% w/w, respectively). The deviation from the previously reported linear relationship between y0 and C0 can be attributed to the assumption that the material with plasticizers is a ‘dilute solution’ at high material-phase concentrations, which likely becomes invalid at these high levels. Preliminary results also show that the plasticizers are ideally mixed in the polymer and that their simultaneous presence does not affect the y0 of individual compounds, even at relatively high material-phase concentrations.